2018
DOI: 10.1101/376046
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combinatorial Genetic Control of Rpd3S through histone H3K4 and H3K36 Methylation in Budding Yeast

Abstract: 1Much of euchromatin regulation occurs through reversible methylation of histone H3 2 lysine-4 and lysine-36 (H3K4me and H3K36me). Using the budding yeast Saccharomyces 3 cerevisiae, we previously found that levels of H3K4me modulated temperature sensitive alleles 4 of the transcriptional elongation complex Spt6-Spn1 through an unknown H3K4me effector 5 pathway. Here we identify the Rpd3S histone deacetylase complex as the H3K4me effector 6 underlying these Spt6-Spn1 genetic interactions. Exploiting these Spt6… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Analysis of the 17 extragenic suppressors identified mutations in seven genes, all of which encode factors that regulate transcription elongation and chromatin ( Figure 2A). Four of these genes -SET2, RCO1, CHD1, and HTA1 -were previously identified as suppressors of either spt6 mutations or mutations that impair related elongation factors (Chu et al, 2006;Keogh et al, 2005;Lee et al, 2018;McCullough et al, 2015;Quan and Hartzog, 2010). As three of the genes, SET2, RCO1, and CHD1, are nonessential for viability, we tested complete deletions of each and found that they also suppressed spt6-YW, showing that suppression is conferred by loss of function (Table S2).…”
Section: Suppressors Of Spt6-yw Identify Important Transcription Elonmentioning
confidence: 93%
See 1 more Smart Citation
“…Analysis of the 17 extragenic suppressors identified mutations in seven genes, all of which encode factors that regulate transcription elongation and chromatin ( Figure 2A). Four of these genes -SET2, RCO1, CHD1, and HTA1 -were previously identified as suppressors of either spt6 mutations or mutations that impair related elongation factors (Chu et al, 2006;Keogh et al, 2005;Lee et al, 2018;McCullough et al, 2015;Quan and Hartzog, 2010). As three of the genes, SET2, RCO1, and CHD1, are nonessential for viability, we tested complete deletions of each and found that they also suppressed spt6-YW, showing that suppression is conferred by loss of function (Table S2).…”
Section: Suppressors Of Spt6-yw Identify Important Transcription Elonmentioning
confidence: 93%
“…Spt16 and Pob3 are the two subunits of the histone chaperone FACT (Gurova et al, 2018), and Spt5 is a conserved elongation factor that interacts directly with RNAPII and has recently been implicated in controlling chromatin structure (Crickard et al, 2017;Ehara et al, 2019;Hartzog and Fu, 2013). The identification of spt6-YW suppressors in SPT16, POB3, and SPT5 was unexpected, as previously isolated mutations in these genes conferred similar, rather than opposite phenotypes as spt6 mutations (Cheung et al, 2008;Hainer et al, 2011;Hartzog et al, 1998;Jeronimo et al, 2019;Jeronimo et al, 2015;Kaplan et al, 2003;Lee et al, 2018;Malone et al, 1991;McCullough et al, 2015;Morillo-Huesca et al, 2010;Pathak et al, 2018;Swanson and Winston, 1992). The analysis of the FACT and Spt5 suppressors is the focus of the rest of these studies.…”
Section: Suppressors Of Spt6-yw Identify Important Transcription Elonmentioning
confidence: 99%
“…2015) or that impair other chromatin-related factors, including FACT, Swi/Snf, Set2, and Rpd3S (Z hang et al . 2008; L ee et al . 2018b; V iktorovskaya et al .…”
Section: Introductionmentioning
confidence: 99%
“…Second, in vivo, a temperature-sensitive spn1 mutation, spn1-K192N (FISCHBECK et al 2002), causes changes in chromatin structure, resulting in altered spacing between nucleosomes and increased nucleosome fuzziness (VIKTOROVSKAYA et al 2021). Third, spn1-K192N is suppressed by mutations that alter histone H2A (MCCULLOUGH et al 2015) or that impair other chromatinrelated factors, including FACT, Swi/Snf, Set2, and Rpd3S (ZHANG et al 2008;LEE et al 2018b;VIKTOROVSKAYA et al 2021). Finally, spn1 mutations cause double mutant sickness or lethality when combined with mutations that impair other histone chaperones (LI et al 2018) or histone H3K4 methylation (LEE et al 2018a).…”
Section: Introductionmentioning
confidence: 99%